(untitled) (gjstudies, 2017)
This research investigates the underexplored nexus between the temporal orientation of investor relationships and the qualitative dimensions of corporate financialdisclosure. Departing from conventional studies that treat investors as a homogeneousgroup or focus primarily on institutional ownership percentages, we propose a novelconceptual framework that categorizes investor relationships along a continuum fromtransactional to transformational, based on investment horizon, engagement depth,and informational symbiosis. We hypothesize that firms with a preponderance of longterm, relationally-embedded investors (termed ’transformational investors’) will exhibitfinancial disclosure practices characterized by greater forward-looking orientation, enhanced transparency regarding strategic trade-offs and intangible assets, and a highertolerance for the disclosure of interim negative performance, compared to firms dominated by short-term, transactional investors. To test these propositions, we develop anoriginal, multi-method methodology. First, we construct a proprietary ’Investor Relationship Horizon Index’ (IRHI) using a combination of machine learning text analysisof investor communication transcripts, analysis of shareholder registry turnover, and asurvey of corporate investor relations officers. Second, we employ a novel ’DisclosureQuality Depth’ (DQD) metric that moves beyond disclosure quantity to assess thestrategic usefulness, contextual richness, and temporal orientation of financial reportsand voluntary disclosures. Applying this framework to a longitudinal dataset of SP500 firms from 1998 to 2004, our results reveal a statistically significant and economically meaningful positive association between a firm’s IRHI score and its DQD metric.Furthermore, we find that this relationship is moderated by industry volatility and mediated by reduced managerial myopia. The study contributes a new theoretical lens forunderstanding disclosure behavior, grounded in relational contracting and stewardshiptheory, and offers practical implications for regulators advocating for long-termism incapital markets and for corporate boards structuring their investor base.